Additive manufacture of an in vitro neuron biosensor - Paul, Benjamin T. (2019)
Two photon polymerisation is presented as a fabrication technique for advancing in vitro neuron biosensors, primarily by coordinating the topology of the cultured neurons but also by developing microstructures capable of monitoring the soluble environment of the cultured neurons. A substrate treatment protocol was developed to facilitate the adhesion of an in vitro neural culture in the presence of two photon polymerised microstructures of a commercially available organically modified ceramic (Ormocer), called OrmoComp. A method for promoting the adhesion of neurons to gold rather than glass was developed using a thiol containing cyclical peptide motif known for promoting cell adhesion, arginine glycine aspartate (cRGD). The two photon polymerisation of OrmoComp was optimised by developing a modular design and performing parameter optimisation sweeps on a single unit of the design, allowing for larger neural guidance structures to be made by two photon polymerisation than previously possible. Dissociated rat hippocampal neurons were seeded, cultured and imaged in the presence of OrmoComp microstructure designs to coordinate their structural and functional topology. Although phase contrast micrographs suggested that the culture had been successfully coordinated, calcium imaging and scanning electron microscopy indicated that the microculture of neurons within the microstructure were functionally connected to the surrounding macroculture. Hydrogel microstructures containing a combination of fluorophores capable of ratiometrically measuring the pH of the solution were produced using a polyethylene glycol diacrylate and a water soluble two photon compatible photoinitiator. This thesis integrated existing processes from a wide range of disciplines ranging from cell culture, chemical synthesis and manufacturing engineering. The progress made applying two photon polymerisation to neuron biosensors was underpinned by advancements in the implementation of two photon polymerisation through improvements in software, hardware and photochemistry. This thesis concludes that the continued development of two photon polymerisation will provide the neuron biosensor community, and the wider tissue engineering community, with new tools to build and monitor artificial tissue.